Do People Like Mandatory Rules? The Choice Between Disclosures, Defaults, and Mandatory Rules in Supplier‐Customer Relationships. Issue 2 (25th June 2021) - Katz, Ori; Zamir, Eyal
Abstract : In recent years, numerous empirical studies have examined the prevailing attitudes toward nudges, but hardly any have examined the prevailing attitudes toward mandatory rules. To fill this gap, this article describes five studies ( N  = 3, 103)—mostly preregistered studies conducted with representative samples of the U.S. population—which tested people's attitudes toward mandatory rules in contractual settings. We found that in supplier‐customer relationships, people tend to rate mandatory rules as more desirable than disclosure duties and default rules. People's judgments in this regard depend on the relative effectiveness of the various types of rules in protecting customer's interests and their expected impact on the price, but there is considerable support for mandatory rules even if they are only slightly or moderately more effective than the alternatives, and even when they entail some price increase. People tend to believe that mandatory rules in this sphere enhance customers' freedom of contract—which may explain why these judgments are not correlated with people's ideological inclinations (liberal or conservative).